Simultaneous or sequential administration of botulinum neurotoxin E does not reduce the duration of paralysis caused by botulinum neurotoxin A in rat EDL muscle. (18th March 2011) - Adler, Michael; Deshpande, Sharad S.; Apland, James P.
Exposure to botulinum neurotoxin serotype A (BoNT/A) or serotype E (BoNT/E) results in muscle paralysis owing to cleavage of the SNARE protein SNAP-25 between residues 197-198 or 180-181, respectively. Although SNAP-25 is the substrate for both serotypes, the duration of paralysis is considerably longer for muscles exposed to BoNT/A. This study was designed to determine whether paralysis times were determined by differences in the half-lives of the truncated SNAP-25 fragments or by differences in the persistence of the respective BoNT light chain (LC) within the nerve terminals.